Factor Affecting Customer’s Intention to Use Mobile Banking Service at Private Bank in Indonesia - Nilo Legowo, Richman Tumpal Micael Pakpahan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The rapid development of technology in Indonesia today resulted in very tight competition in the industrial world, where industry players are required to be able to provide faster and efficient services to keep their consumers from turning to competitors. PT. XYZ Bank In 2014 launched a mobile banking service called SimobiPlus. However, based on the data obtained from the number of internal SimobiPlus users, it is still below 15% of the total customers and it can be concluded that the use intention between customers is still very low, so the authors want to find out the factors that influence the user's intention to use. These research analysts used the method of the previous research UTAUT Extend, where this method has been proven on conducting research of intended use and modify it by adding a variable perception of usefulness, ease of use, trust, and security. In collecting the data, questionnaires with 400 respondents also use for the analysis of this research. Based on the results, the variable Perceived Ease of Use, Trust, Security, Social Influence has a positive effect on behavioral intention, where the Perceived Usefulness variable has the top influence among the variables used in this research.